Determinan Kejadian Hipertensi pada Ibu Hamil Di Puskesmas Purwokerto Utara II - Ikit Netra Wirakhmi; Tin Utami; Dwi Agus Yulianto (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Maternal Mortality Rate (MMR) is an indicator to see the success of maternal health efforts. MMR in Banyumas Regency in 2019 was 38 per 100,000 live births and in 2020 it was 41.55 per 100,000 live births. The most common causes of MMR in Banyumas Regency are preeclampsia, bleeding during pregnancy, childbirth and the puerperium accompanied by complications from comorbidities. Maternal deaths usually occur because of the high cases of pregnant women with high risk. Factors that influence the incidence of preeclampsia can be interrelated and influence one another. Knowing the risk factors for hypertension in pregnancy is useful for the health care system for pregnant women to monitor risk groups from early pregnancy to the second trimester. The purpose of this study was to determine the determinants of the incidence of hypertension in pregnant women at the North Purwokerto II Health Center. The research design is a cross sectional study. Respondents in this study were pregnant women at the Purwokerto Utara 2 Public Health Center, Banyumas Regency. Data was taken in August - September 2022 using a questionnaire and direct blood pressure measurements. Samples were taken using total sampling technique with a total of 67 respondents. Statistical tests used univariate analysis (frequency distribution) and bivariate analysis using the fisher's exact formula (p <0.5). The results of this study were that there were no factors related to the incidence of hypertension in pregnant women at the Purwokerto Utara II Health Center with a p value > 0.05. There is no relationship between maternal age, gestational age, parity, occupation, education level, socioeconomic status, family history of hypertension, overweight and use of contraceptives with hypertension in pregnant women at the Purwokerto Utara II Health Center.